1958
DOI: 10.2307/1942207
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Reproductive Behavior and Ecology of Fourteen Species of Darters (Pisces‐Percidae)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecological Monographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
2

Year Published

1976
1976
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(142 citation statements)
references
References 23 publications
4
136
2
Order By: Relevance
“…Constantz 1979). resembled the male mating act of the more primitive species of darters (Winn 1958a).…”
Section: Territorial Behaviourmentioning
confidence: 92%
See 2 more Smart Citations
“…Constantz 1979). resembled the male mating act of the more primitive species of darters (Winn 1958a).…”
Section: Territorial Behaviourmentioning
confidence: 92%
“…Male johnny darters were perhaps shifting from a sexual to a parental phase as reported for sticklebacks (Assem 1967, Iersel 1953, Morris 1958) and sunfishes (Colgan & Gross 1977). The presence of eggs in the nest may have been the triggering stimulus (see Bol 1959, Kramer 1973 since Winn (1958a) induced parental care activities by placing eggs in the nest of a male that had not previously spawned. The behavioural change in the johnny darter seemed less rigid compared to sticklebacks or sunfishes since some darters mated throughout the reproductive cycle.…”
Section: Displays To Conspecificsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, taxonomists (Bailey & Gosline 1955, Collette 1965, Page 1977, Collette & Banarescu 1977 have indicated that Hololepis and Microperca are the most highly evolved subgenera of Etheostoma. Winn (1958b) pointed out apparent conflicts between this behavioral evolution and the taxonomists morphological evolution. Clearly, more behavioral and systematic studies are required to resolve these and other conflicts.…”
Section: Genital Papillaementioning
confidence: 99%
“…Although both use rocky substrates either as shelter from predators (Cracker & Barr 1968, Stein & Magnuson 1976, Rahel & Stein 1988 or as spawning sites (Winn 1958, Downhower & Brown 1980, little is known about how these organisms interact. One particularly interesting problem is how small, cavity-spawning fish such as darters (Percidae) are able to coexist with large, wellarmored predators such as crayfish.…”
Section: Introductionmentioning
confidence: 99%